Análise por refinamento Rietveld do efeito de diferentes tratamentos térmicos em aço ferramenta A2 fabricado por manufatura aditiva - Braghim, Leonardo do Carmo (Universidade Federal de São Carlos, 2023)
The Laser Powder Bed Fusion (L-PBF) is an additive manufacturing technique in which a part is built layer by layer. This process is used for producing parts with complex geometries and customizable densities, such as prosthetics, structural components for aircraft and vehicles, or molds and dies for other manufacturing processes. The heat treatment commonly used to increase the hardness of A2 tool steel leads to the loss of refined microstructure when applied to metals manufactured through additive manufacturing. Therefore, due to the peculiar characteristics of additive manufacturing processes, it becomes necessary to develop non-standard heat treatments that increase hardness without compromising the microstructure resulting from the manufacturing process. The objective of this study is to analyze the X-ray diffraction patterns obtained from A2 tool steel parts fabricated using L-PBF for four different heat treatments: modified normative treatment at 540°C, modified normative treatment at 205°C, shallow sub-zero treatment, and, for comparison purposes, the normative treatment used in conventional manufacturing. Similarity was observed among the resulting phases from the heat treatments, with the normative treatment showing the most significant reduction in the retained austenite fraction and lattice parameters. As the atoms gain energy (mobility) with increasing temperature, higher temperatures lead to increased atomic mobility and diffusion, resulting in the rearrangement of atoms within the unit cells and favoring stress relief during tempering. Consequently, samples subjected to higher temperature treatments exhibited a more considerable reduction in lattice parameters.
Rietveld refinement analysis of the effect of different heat treatments on A2 tool steel manufactured by additive manufacturing
Keywords: Tratamento Térmico; Heat treatment; Refinamento Rietveld; Rietveld refinement; Aço ferramenta A2; A2 tool steel; Fusão em leito de pó a laser; Laser powder bed fusion; Manufatura aditiva; additive manufacturing; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA FISICA